2017
DOI: 10.1126/sciadv.1701222
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-triggered physically transient electronics

Abstract: We present a type of electronics that can be dissolved upon the presence of moisture within a controllable time scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
131
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 32 publications
1
131
0
Order By: Relevance
“…The biodegradability of the electronic system eliminates a second surgery for device retrieval and, therefore, could reduce potential risks and chronic inflammation caused by permanent devices, as well as associated hospital costs. Other potential applications include eco‐friendly devices that alleviate issues (e.g., landfill space and hazardous components) associated with electronic‐waste (e‐waste) and data‐secure hardware systems that prevent unauthorized access to personal or security information . Translation of these technologies could potentially provide vital tools that are beneficial for human healthcare and the environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradability of the electronic system eliminates a second surgery for device retrieval and, therefore, could reduce potential risks and chronic inflammation caused by permanent devices, as well as associated hospital costs. Other potential applications include eco‐friendly devices that alleviate issues (e.g., landfill space and hazardous components) associated with electronic‐waste (e‐waste) and data‐secure hardware systems that prevent unauthorized access to personal or security information . Translation of these technologies could potentially provide vital tools that are beneficial for human healthcare and the environment.…”
mentioning
confidence: 99%
“…The degradation rates of biopolymers depend on their specific chemistry, molecular weight, terminal groups, etc. ; for example, partially oxidized alginate losses 70% of molecular weight within 5 d, PLGA (65:35) losses 50% of mass after ≈18 d, while polyanhydride fully degrades within 48 h in moisturized environments . Although MoO 3 is expected to dissolve quickly in aqueous solutions due to its high solubility (≈1 g L −1 ), its degradation rate is modulated by the PLGA binder and encapsulation layers.…”
mentioning
confidence: 99%
“…Other strategies, such as overcoats of inactive encapsulation layers, regulation of properties, and dimensions of active materials, can be exploited to control the transience time in function . Beyond dissolution control with prescribed time span in a passive manner, actively programmable and on‐demand controlled degradations are possible via optical sources, temperature, and a series of chemical reactions . Figure b presents a schematic description and transient circuit diagram of in vitro demonstration for a tunable lifetime of a dissolvable integrated circuit in response to optical stimuli using commercial light‐emitting diodes (LED) connected with Mg electrodes/interconnects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gao et al reported moisture‐triggered transient electronics that can physically disappear within controlled time frames. This transient system was based on the fact that the moisture‐triggered hydrolysis of the polyanhydride substrate employed generated corrosive organic acids, which subsequently destroyed electronic components and substrates . Our previous work illustrated a thermoresponsive transient mode by leveraging composites of thermoresponsive polymers and conductive silver nanowires (AgNWs) to form transient conductive traces, resistors, and parallel plate capacitors.…”
Section: Introductionmentioning
confidence: 99%